2011
DOI: 10.1073/pnas.1100285108
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo fluorescence imaging of exogenous enzyme activity in the gastrointestinal tract

Abstract: Exogenous enzymes are administered orally to treat several diseases, such as pancreatic insufficiency and lactose intolerance. Due to the proteinaceous nature of enzymes, they are subject to inactivation and/or digestion in the gastrointestinal (GI) tract. Here we describe a convenient fluorescence-based assay to monitor the activity of therapeutic enzymes in real time in vivo in the GI tract. To establish the proof of principle, the assay was applied to proline-specific endopeptidases (PEPs), a group of enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…This can lead to mental retardation if the disease is untreated in early childhood [143]. Another example of enzyme deficiency is germline mutations in genes coding for DNA repair enzymes which cause hereditary cancer syndromes such as xeroderma pigmentosum [144]. Defects in these enzymes cause cancer since the body is less able to repair mutations in the genome.…”
Section: Modern Application Of Enzyme: a Biotechnology Viewmentioning
confidence: 99%
“…This can lead to mental retardation if the disease is untreated in early childhood [143]. Another example of enzyme deficiency is germline mutations in genes coding for DNA repair enzymes which cause hereditary cancer syndromes such as xeroderma pigmentosum [144]. Defects in these enzymes cause cancer since the body is less able to repair mutations in the genome.…”
Section: Modern Application Of Enzyme: a Biotechnology Viewmentioning
confidence: 99%
“…Technically, even more demanding than measuring food intake is the quantification of nutrient digestion, as there is no direct optical access to the gastrointestinal tract in most species. More specialized technologies, such as bioluminescence, MRI, or computed tomography, have been valuable to generate insights into in vivo dynamics of digestive function (10,18,19,31). However, all of these methods require immobilization of the experimental subject to reduce motion artifacts, thereby making concurrent behavioral observations impossible.…”
mentioning
confidence: 99%
“…Leroux and co-workers recently demonstrated that the functionality of different polymers grafted to proline-specific endopeptidases could be manipulated to stabilize and alter the dwell time of orally administered enzymes at different locations in the gastrointestinal tract 10 . Such studies are crucial because trends and observations made in vitro often do not correlate with in vivo observations 11 . This is in part due to the complex and potentially unpredictable nature of the interactions between the conjugate and components of the body.…”
mentioning
confidence: 99%